Stosunek halachy do relacji lesbijskich. Na marginesie - Janczewska, Aleksandra (Humaniora. Czasopismo Internetowe, 2025)
This article examines the evolution of halakhic approach to lesbian relationships in rabbinic sources over the centuries. Using a diachronic framework, it analyzes early midrashim (Sifra, Genesis Rabba, Leviticus Rabba), passages from the Babylonian and Jerusalem Talmuds (Yevamot 76a), and medieval halakhic codes (Rashi, Maimonides, Tur Even HaEzer, Shulchan aruch). Employing critical discourse analysis, the study traces shifts in how female homoeroticism was defined, judged, and sanctioned. The analysis also reveals rhetorical strategies that equate lesbian relations with foreign customs to justify social and religious distancing.